THE EFFECT OF USING BLENDED LEARNING STRATEGY ON ACHIEVEMENT AND ATTITUDES IN TEACHING SCIENCE AMONG 9TH GRADE STUDENTS - Almasaeid, Turki Fahed (European Scientific Journal, ESJ, 2014)
The aim of this study represented by identifying the impact of teaching science using blended learning strategy in the development of achievement skill among students. The study focused on the students in the ninth grade in Dubai Educational zone in the first semester of the year 2013/2014. Sample has been selected from Omar Bin Al-Khattab intermediate School (45) students. The school has been chosen as it provided a computer lab, e-learning equipment and tools to accommodate the number of students. A subject has been designed from the first unit in science to the ninth grade and it was followed by an achievement test which consists of a multiple choice study before and after applying the educational program. Along with these tests, a questionnaire was prepared in order to measure student’s attitudes. To justify our calculation, the results were manipulated by analysis of covariance (ANCOVA) along with analysis of variance (ANOVA). These calculations conclude our finding to the following: the results and its analysis show that the two groups, one of them under traditional teaching method and the other using blended learning strategy. Using blended learning strategy to teach science, has a positive impact in achievement skill and attitudes. The study showed high level of performance on achievement test as a whole after applying blended learning strategy. At the end of this study, many issues required more researcher’s attention, so, in the light of these findings, we provide recommendations in various areas.